The Pelatihan Inovasi Produk Pempek dengan Penambahan Sayuran pada Pelaku UMKM Kelurahan Cipedak Jakarta Selatan - Almira Nuraelah; Khoirul Anwar; Hamidatun Hamidatun; Syafiqa Suhaila; Winda Zahraningrum (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Pempek is a traditional food originated from Palembang, South Sumatera and popular to all Indonesian people. Small and Medium Enterprises (SMEs) in Cipedak, South Jakarta is one of the SMEs that produce mackerel based pempek products. Technological advances encourage SMEs actors to do innovation in order to increase the selling value of pempek products.This community service activity aims to provide knowledge and training to SMEs actors about innovations in producing pempek with addition of vegetables. The implementation method is consist of counseling about the ingredients used in producing pempek with addition of vegetables, direct practicing of produce pempek, and assessing the level of preference for vegetable pempek products with preference tests. This training succeeded in increasing the skills and knowledge of the participants, especially in the development of delicious and nutritious pempek products. Besides, the hedonic test results showed that pempek product with addition of vegetables were favored by participants in terms of color, smell, taste and texture. This training is expected to be the beginning of the development pempek products with more selling value to the pempek business community, especially in Cipedak, South Jakarta.